EFEKTIVITAS KELOMPOK MASYARAKAT PEDULI API (MPA) DALAM MELAKSANAKAN PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN DI DISTRIK KEBAR - Yonathan Kalua’ Payung Allo; , Rima Herlina S. Siburian; Jonni Marwa (Universitas Lambung Mangkurat, 2021)
Forest and land fire prevention measures are the most important component of the entire forest and land fire suppression system. Even though Tambrauw Regency, especially in the Kebar district, is not yet an area prone to forest and land fires, how effective is the implementation of community group activities concerned with fire in this area and how the community's perceptions are in its prevention and control, it is necessary to conduct research as a basis for future management of this district. This research was conducted in Manarai and Jafai villages, Kebar district, using the interview method. Data collection techniques for internal factors and external factors that influence people's perceptions and participation are recorded and adjusted for the variables and the scores are calculated to determine the low, medium or high categories and descriptive and qualitative analyzes are carried out. The results of this study indicate that the formation of a fire-care community group in Kebar District did not provide satisfactory results because it had not yet reached the national medium-term target to be achieved in preventing forest and land fires, namely a reduction in the number of hotspots by 10% and a decrease in the number of burned areas by 10%. in 2019 from the 2015 baseline. However, when viewed from the indicators of community perceptions in preventing forest and land fires, it is quite good. Even the socio-economic aspects of the community do not affect the value of the community's perception of preventing forest and land fires in Kebar District.